Magnetic fields do not suppress global star formation in low metallicity dwarf galaxies - Whitworth, David J.; Smith, Rowan J; Klessen, Ralf S.; Mac Low, Mordecai-Mark; Glover, Simon; Tress, Robin; Pakmor, Rüdiger; Soler, Juan D. (Monthly notices of the Royal Astronomical Society, 2023)
Many studies concluded that magnetic fields suppress star formation in molecular clouds and Milky Way like galaxies. However, most of these studies are based on fully developed fields that have reached the saturation level, with little work on investigating how an initial weak primordial field affects star formation in low metallicity environments. In this paper, we investigate the impact of a weak initial field on low metallicity dwarf galaxies. We perform high-resolution arepo simulations of five isolated dwarf galaxies. Two models are hydrodynamical, two start with a primordial magnetic field of 10−6μG and different sub-solar metallicities, and one starts with a saturated field of 10−2μG. All models include a non-equilibrium, time-dependent chemical network that includes the effects of gas shielding from the ambient ultraviolet field. Sink particles form directly from the gravitational collapse of gas and are treated as star-forming clumps that can accrete gas. We vary the ambient uniform far ultraviolet field, and cosmic ray ionization rate between 1 per cent and 10 per cent of solar values. We find that the magnetic field has little impact on the global star formation rate (SFR), which is in tension with some previously published results. We further find that the initial field strength has little impact on the global SFR. We show that an increase in the mass fractions of both molecular hydrogen and cold gas, along with changes in the perpendicular gas velocity dispersion and the magnetic field acting in the weak-field model, overcome the expected suppression in star formation.